GENERAL SOCIAL EXPLOITATION OF CHILDREN IN UKRAINE: MAIN DIRECTIONS AND WAYS TO SOLVE THE PROOBLEM - Доляновська, І. М. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The article reveals the essence and main directions of preventing such a negative phenomenon as the exploitation of children in Ukraine, namely one of such directions - the general social.